COVERT AGE DISCRIMINATION: THE PHENOMENON OF AGEISM AGAINST YOUNG WORKERS IN THE INDUSTRIAL SECTOR - Nurul Inayah Zul Putri; Rahman Malik (Academic Solution Publisher, 2025)
This study aims to analyze in depth the phenomenon of ageism experienced by young workers in the industrial sector. This issue is rarely discussed, as previous studies have tended to focus on age discrimination experienced by older people. Using a qualitative approach and case study design, this study examines experiences of ageism among workers aged between 25 and 35 years. Data collection was conducted through in-depth interviews and research from written sources to strengthen the existing theoretical framework. Findings from this study indicate that ageism against young workers manifests in the form of discrimination during the recruitment process, negative stereotypes about their abilities and character, and seniority practices that make age an indication of authority and competence. Structural factors such as traditional work hierarchies and cultural norms regarding the age of marriage also reinforce these age discrimination practices. In terms of theory, this study contributes to expanding the understanding of ageism by emphasizing that age discrimination can occur not only against older workers but also against young workers, thus necessitating a more inclusive analytical framework. Empirically, the results of this study underscore the importance of policy interventions and improvements in work culture in order to create a more inclusive industrial environment that is free from age discrimination.